Lateral sediment transport and late Quaternary changes of eolian sedimentation in the East Sea (Japan Sea). (1st April 2021) - Bahk, Jang-Jun; Um, In-Kwon; Jang, Jun-Ho
Graphical abstract: Highlights: GSDs reveal offshore limit of lateral sediment transport in the East Sea. Lateral sediment transport from the Korean Peninsula is within 70 km offshore. Eolian sediments in the SKP were transported by upper westerlies and winter monsoons. East Asian winter monsoon intensity controlled eolian sedimentation in the East Sea. Abstract: We investigated grain size records of a sediment core (05-P21) from the South Korea Plateau in the East Sea, located ca. 270 km east of the east coast of the Korean Peninsula. To verify an exclusive eolian origin for the detrital components of the sediments, we first examined how far offshore lateral-sediment-transport contributions from the eastern margin of the Korean Peninsula could reach, based on spatial changes in the grain size distribution (GSD) of surface sediments. To distinguish grain populations representing different transport processes, we performed end-member analyses (EMAs) of the GSDs of detrital fractions using the AnalySize software. EMA of the surface sediment GSDs showed that they consist of three end-member (EM) grain populations representing contributions from lateral (EM1 and EM2) and eolian transport (EM3). EM contributions by lateral transport reached only ca. 70 km seaward, confirming the exclusive eolian origin of detrital components of the 05-P21 core sediments. EMA of GSDs of the 05-P21 sediments distinguished two EM grain populations with fine (3.6 µm) and coarse (9.5 µm) median sizes, suggesting transport by upper westerlies and winter monsoon northwesterly surface winds, respectively. Variation in the proportions of fine and coarse EMs since ca. 186 ka indicated controls by both orbital and sub-orbital scale changes in intensity of the East Asian winter monsoon in association with global ice volume changes and Dansgaard–Oeschger cycles.